Work-life Balance towards Employee Well- being and Productivity in Malaysia Private Sector - Ang, Hun Yong; Wong, Bao San; Cheah, Jui Ying; Subhashini, Jayakumar; Jason Lu, Kiing Choung; Yi, Na (INTI International University, 2024)
To date, work-life balance (WLB) has been a focus topic especially towards the work and family domains. With the change of workplace psychology and value mapping, the current workforce heterogeneously, workforce nowadays may value it beyond family. This study is looking to discover and determine work-life balance among Malaysian working adults. The focus is on the relationship of flexibility, motivation, job satisfaction, workplace support, and technological adaptation. Through a survey of 100 participants, this research uncovers key factors contributing to work-life balance, offering insights for employers and policymakers to enhance employee wellbeing and productivity in Malaysia. The findings highlight the significance of tailored workplace practices that address these determinants to foster a balanced and healthy work environment.